Kajian Pedagogis - Sosiologis Terhadap Tradisi Penangkapan Ikan Oleh Kaum Perempuan di Pulau Ndao, Kabupaten Rote Ndao - Luji, Daud Saleh (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The aim of this research is to find out the fishing traditions carried out by women on Ndao Island, and to analyze the pedagogical-sociological values contained in these fishing traditions which need to be passed on to the next generation. To obtain information, the research method used was a qualitative method by interviewing 5 people as resource persons who understood the fishing traditions on Ndao Island. The results obtained from this research are that there are a number of fishing traditions carried out by women on Ndao Island, namely Dja'i, Lege tatohi, Hèb'bi, Pasèra and Bhabho. From this tradition there are a number of pedagogical and sociological values that are obtained and need to be passed on to future generations, namely: 1). Men learn to respect women's work, 2). The equipment used to catch fish is the kalera and kanaca, and these two tools are used as symbols of marriage. 3). People are taught to be patient and diligent in doing a job. 4) The community learns from the Ndao women to always work together in doing work. 5). The community is taught to use sea-friendly fishing methods. 6). Learn to share results as a form of manifestation of love for others.